A role of microRNA‐370 in hepatic ischaemia‐reperfusion injury by targeting transforming growth factor‐β receptor II. (9th January 2014) - Li, Lan; Li, Guogang; Yu, Chaohui; Shen, Zhe; Xu, Chengfu; Feng, Zhiying; Zhang, Xuequn; Li, Youming
Abstract Background & Aims MicroRNAs (miRNAs) are a group of small non‐coding RNAs with modulator activity of gene expression. The role of miRNAs in hepatic ischaemia‐reperfusion (IR) injury is currently largely unknown. The aim of this study was to investigate the potential role of miR‐370 in hepatic IR injury. Methods The expression levels of hepatic miR‐370 in male C57BL/6 mice subjected to hepatic IR injury or ischaemia preconditioning were assessed by quantitative real‐time PCR. The effect of miR‐370 on hepatic IR injury was investigated by serum enzyme analysis and histological examination of liver following treatment of mice with antagomir‐370 or control. The levels of proinflammatory cytokines and apoptosis‐ and proliferation‐related genes were also determined by quantitative real‐time PCR. Furthermore, the potential targets of miR‐370 in this injury were studied by bioinformatics analysis, luciferase assays, quantitative real‐time PCR and Western blot. Results The results showed that miR‐370 expression was significantly upregulated in the mice subjected to hepatic IR injury as compared with the sham‐operated mice. Inhibition of miR‐370 led to the downregulation of serum aminotransferase and proinflammatory cytokines, as well as the improvement of hepatic histological damage. Reporter assays confirmed that miR‐370 directly targeted the 3′ untranslated region of transforming growth factor‐β receptor II (TβRII). Inhibition of miR‐370 was sufficient to reinstate the expression of TβRII and its downstream target phosphorylated Smad3. Conclusion Our data suggest that miR‐370 acting via TβRII might play a potential role in hepatic IR injury, and inhibition of miR‐370 efficiently attenuated the damage to the liver.